Islamic Education Teachers’ Strategies in Addressing Verbal Bullying among Elementary School Students - Mira Silvia; Zulfani Sesmiarni (STIT Ahlussunnah Bukittinggi, 2026)
This study examines the roles and strategies of Islamic Religious Education teachers in addressing verbal bullying among elementary school students, which still occurs in the form of taunts, inappropriate name-calling, and jokes that hurt their peers’ feelings. The study aims to describe the strategies teachers use to address this issue through counseling, behavior contracts, and parental involvement. This study employs a qualitative approach using a case study design, with subjects including Islamic Religious Education teachers, students involved in verbal bullying, and the students’ parents. Data collection techniques include observation, interviews, and documentation, while data analysis utilizes the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions. The results of the study indicate that the handling of verbal bullying is carried out in stages, beginning with counseling based on Islamic moral values, followed by a behavioral contract as a form of agreement to improve behavior within a specific timeframe, and if no change occurs, involving parents to conduct joint guidance at home and at school. The conclusion of this study indicates that the strategies employed by Islamic Religious Education teachers are phased and collaborative among teachers, students, and parents, and place greater emphasis on character development rather than merely imposing sanctions.